(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this study was to analyse and to assess the diversity of households’ incomes and households’ savings in different regions in Poland . The value and the structure of average monthly available income per capita in household were taken into consideration. Also, savings and saving rates for households from various regions were compared. In order to reach the planned objective, the subject-matter literature was analysed, the method of presentation and assessment of the collected data was used via basic statistical tools. The key sources of information were statistical data of the Central Statistical Office in Poland, for the years 2008-2016. After completing the research, it was found that: a) the highest average level of income and savings was characteristic for the households from the central region, the lowest - for the households from the eastern region; b) the highest average income growth rate was noted for the households from the southern region, the lowest - for the households from the central region; c) the households located in the central region, as the only households within the entire period covered by the analysis, made an income higher than average income for the households in Poland; d) irrespective of the location of the household, the main source of income was salary. An important source of income were also social benefits; e) the highest propensity to save, measured by the savings rate from available income, was characteristic for households from the north-western region, the lowest – from the south-western region. The results reveal differences of both income and savings in households in various regions in Poland.